PELAPORAN KEUANGAN UMKM BERDASARKAN SAK EMKM (Studi Kasus pada UMKM di PD Pasar Jaya Kramat Jati) - Tina Setyaningsih; Khoirina Farina (POLITEKNIK LP3I JAKARTA, 2021)
The purpose of this research is to statistically examine the factors that influence the preparation of MSMEs financial reporting based on SAK EMKM at PD Pasar Jaya Kramat Jati. The data in this study are primary data, obtained through the distribution of questionnaires totaling 85. Due to special consideration in accordance with predetermined criteria, Therefore the sampling technique uses purposive sampling in this study. Processing in the study uses SmartPLS 3.3.2 software. The result of this study shows that there is evidence that the variables of educational background and business scale have a positive and significant impact on MSMEs financial reporting based on SAK EMKM. While other variables in this study namely accounting understanding and do not have significant influence on MSMEs financial reporting based on SAK EMKM.Key words: SAK EMKM, Financial reporting, UMKM